Adaptive control of a Wiener type system: application of a pH Neutralization reactor - Figueroa, Jose Luis (2007)
In this paper the problem of on-line identification and adaptive control of a Wiener type non-linear system is studied. First, a Wiener model is defined whose linear and non-linear parts are described using Laguerre and piecewise linear basis functions, respectively. Then, an adaptive identification algorithm for this model is presented. A local convergence analysis for the adaptive identification is performed. The model obtained is used to adapt the parameters of a controller designed for the specific structure of the model. The complete scheme is applied to a simulation of a pH neutralization reactor subject to several perturbations. The results show the improved behaviour of the proposed scheme compared with other approaches found in the literature.